2021
DOI: 10.1021/acsnano.1c08690
|View full text |Cite|
|
Sign up to set email alerts
|

Aptamer-Functionalized Binary-Drug Delivery System for Synergetic Obesity Therapy

Abstract: The targeted delivery of phytochemicals that promote energy expenditure for obesity therapy remains a challenge. This study assembled a functionalized adipo-8 aptamer loaded with allicin using isothermal rolling-circle techniques to form a synergistic adipocyte-targeted binarydrug delivery system for treating obesity. The functionalized adipo-8 aptamer efficiently protected allicin from adsorption, showing significant potential to encapsulate, transport, and release molecular cargos into white adipose tissue. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Previous results suggested that G454 was the most stable quadruplex structure with three G‐tetrad layers in the UCP1 domain. [ 38 ] The nine docking models presented in Figure 3C indicated that baicalin interacted with the G454 quadruplex via conventional hydrogen, van der Waals forces, Pi–Pi interaction, and carbon hydrogens in the grooves of the G454‐folded structures (Figure S15 and Table S4, Supporting Information). The 3T3‐L1 preadipocytes were transfected by the G454‐containing UCP1 sequence‐inserted psiCHECK‐2 plasmid to facilitate Renilla and firefly luciferase expression (Figure 3D).…”
Section: Resultsmentioning
confidence: 99%
“…Previous results suggested that G454 was the most stable quadruplex structure with three G‐tetrad layers in the UCP1 domain. [ 38 ] The nine docking models presented in Figure 3C indicated that baicalin interacted with the G454 quadruplex via conventional hydrogen, van der Waals forces, Pi–Pi interaction, and carbon hydrogens in the grooves of the G454‐folded structures (Figure S15 and Table S4, Supporting Information). The 3T3‐L1 preadipocytes were transfected by the G454‐containing UCP1 sequence‐inserted psiCHECK‐2 plasmid to facilitate Renilla and firefly luciferase expression (Figure 3D).…”
Section: Resultsmentioning
confidence: 99%
“…The micromorphology of NAHs, such as the pore size and the degree of crosslink, have an essential effect on cell uptake. At present, NAHs prepared by RCA can be condensed by polyethyleneimine from a micrometer scale to nanoscale, which provide convenience for NAHs entering into the cell [94]. Using rational design for NAHs and exploring other size-controllable technologies will promote the development of NAHs in cell engineering.…”
Section: Discussionmentioning
confidence: 99%
“…After six weeks of administration to DIO mice, there were significant reductions in triglyceride, total cholesterol, and low-density lipoprotein (HDL) levels and substantial weight loss of approximately 12.8 ± 0.75%. To achieve adipocyte-targeted delivery of allicin, which is a phytochemical capable of inducing browning in adipose tissue, adipo-8 aptamer-modified DNA-nanoflower-allicin framework (NFA) was assembled using the isothermal rolling circle technique, which considerably enhanced the bioactivity and stability of allicin ( Figure 3 ) [ 125 ]. Mechanistic studies have shown that the target of allicin is the G-quadruplex (G4) in the mitochondrial uncoupling protein-1 (UCP1) promoter, and adipo-8 and allicin play a synergistic role in the activation of targeted thermogenic genes.…”
Section: Biomaterial-assisted Anti-obesity Therapymentioning
confidence: 99%